Therapeutic Approach to Correct Hematopoiesis and Anemia in Calves with Nonspecific Bronchopneumonia - Vasiliy Korotkiy; Olga Skornyakova (Journal of Global Innovations in Agricultural Sciences)
The paper describes an effective method to correct hematopoiesis and treat anemia in calves suffering from nonspecific bronchopneumonia. The method involves introducing the Vitamin Plus pine needle feed mix in a dose of 5-20 ml per head once daily for four weeks, starting at 30 days of age. This supplementation increases hemoglobin, hematocrit, the average concentration of hemoglobin in red blood cell and serum iron, while also boosting white blood cell, lymphocyte, and monocyte counts. The results show that adding Vitamin Plus to the diet positively influences anemia correction and improves immune response in calves. This method offers a natural and non-invasive alternative to conventional iron supplements and antibiotic treatments, which often carry risks of side effects and antimicrobial resistance. Implementing this dietary strategy in livestock management could reduce mortality rates, enhance growth performance, and improve farm profitability, making it a valuable addition to modern veterinary practice. Keywords: Iron deficiency anemia, vitamin plus pine needle feed mix, hemosiderosis, iron dextran, gastrointestinal microflora